(untitled) (Geo-Eco-Marina, 2020)
The coherence of substrate is the main factor of stability of the home scars. This dependence is demonstrated by the current impressions in Cornwall, illustrated by the Towan morphotype with the ratio L / w = 1.30, located on the hard rocks of the Bovisand Formation and by the St. Agnes morphotype with the ratio L / w = 1.19, located on hemipelagites of the Porthtowan Formation. The significant morphological difference is supported by the presence of two important features: convex depression bordered by the marginal furrow in the Towan morphotype and concave depression bordered by the marginal ridge in the St. Agnes morphotype.